Is the Latin American and Caribbean capital stock affecting the development of the region? - Santiago, Renato Filipe de Barros (2022)
According to the conclusions of the reports of several international institutions, such as the International Monetary Fund, the Latin American and Caribbean region has suffered from a lack of investment in physical capital in recent decades. This is especially true if one looks at both the levels and the state of their infrastructures. As might be expected, this is not a desirable situation, mainly because, according to the same reports, it can give rise to several harmful effects on the economies of this region. That said, it is natural that there is less and less doubt about the fact that in order to promote the development of the Latin American and Caribbean region, it will, in the near future, have to be able to increase its levels of physical capital. Considering the facts stated above, several essays were prepared in this thesis in order to (1) assess the impacts of physical capital on the development of the region; and (2) help the regional policy makers in the development of their future investment strategies. It was taken advantage of the data on public and private capital that was recently made available by the International Monetary Fund to achieve these objectives. Initially, the idea was only to use the data on the public capital stock since it is the one that is linked to the government's provision of economic and social infrastructure. However, as the private capital stock data was also available, it was also included in the analysis. Why stocks? Because in this way, instead of just accounting for the annual flows of public and private investment (only capital increases), it accounts for the volume of existing capital, as well as for the effects of depreciation. The first essay was based on the historical analysis of the evolution of both types of capital in the Latin American and Caribbean region from 1970 to 2017, in order to be able to verify if there was, in fact, a lack of investment in physical capital in this region. Using the data from the International Monetary Fund, the progress of investment and stocks in this region during the previously stated period was graphically analysed, accompanying this analysis with, pass the redundancy, the analysis of the economic conjuncture of the region and with comparisons with the evolution of the physical capital in similar regions. The results of this analysis seem to confirm the hypothesis that this region suffers from a lack of investment in physical capital, with the Latin American and the Caribbean being characterised by a relatively low level of public investment (especially when compared to similar regions), by a very volatile private investment and by a very slow evolution (in some periods almost constant) of its public and private capital stocks as a percentage of gross domestic product (GDP). After this more descriptive analysis, the three essays that followed were based on empirical analysis applied to Latin American and Caribbean countries panels, in order to study the effects from both capital stocks on the region's economic growth, on the region's income inequality levels and on the region's energy intensity, respectively. In this way, it was possible to evaluate the contributions that public and private capital stocks had in various development fields, namely in the economic, socioeconomic and sustainable fields. Regarding the methodologies that were used, in the second essay of this thesis, where the relationship between the capital stocks and economic growth was investigated, the panel vector autoregressive (PVAR) methodology was used to study the short-run impacts and Granger's causalities, whereas the panel dynamic ordinary least squares (PDOLS) and panel fully modified ordinary least squares (PFMOLS) estimators were used to study the long-run impacts. In the third essay, where the impacts of both capital stocks on income inequality were analysed, the panel autoregressive distributed lag (PARDL) model and the Driscoll-Kraay (DK) estimator with fixed effects were used to study the short- and long-run impacts of the variables. Finally, in the fourth essay, where the role of public capital stock and private capital stock in the region's energy intensity was studied, the panel autoregressive distributed lag (PARDL) model and the Driscoll-Kraay (DK) estimator with fixed effects were again used to study the short- and long-run impacts of the variables. In addition, the log t regression test method and the club clustering algorithm were also used in order to investigate the various convergence clubs in terms of energy intensity, whereas the ordered-logit model was used to verify whether capital stocks were important determinants for the club's formation. The results from the essays seem to indicate that: 1) both public and private capital had a positive effect on the long-run economic growth of the Latin American and the Caribbean countries; 2) in the short-run, public capital seems to have had negative effects on both growth and private capital (crowd-out effect); 3) the capital stock (public, private and total) seems to have contributed to the increase in income inequality in the short-run; 4) in the long-run, this effect seems to disappear (which still does not demonstrate a contribution of physical capital to the reduction of income inequality); 5) both types of capital (public and private) appear to have had an enhancing effect on the long-run energy intensity of the Latin America and the Caribbean countries; 6) the public and private capital stocks did not prove to be determinant factors for the formation of the clubs. Through these results, it can be concluded that there is, in fact, a lack of investment in physical capital in Latin America and the Caribbean and that, therefore, in order to promote the development of the region, regional governments should increase their investment levels (through better financing methods) and create conditions to attract private investment, at the same time as they develop strategies that allow to public and private capital to act as complements. They should also improve the quality of their investment projects, as well as their selection criteria, channelling a significant part of the new investments to the poorest/underdeveloped areas, creating incentives for private investment also to reach these areas. Finally, they must ensure that the new physical capital is more energy-efficient and should create measures to encourage the private sector to follow this same trend.